Interface cracks in piezoelectric materials - Govorukha, Volodymyr; Говоруха, Володимир Борисович; Kamlah, M.; Камла, М.; Loboda, V.; Лобода, В.; Lapusta, Y.; Лапуста, Ю. (IOP Publishing Ltd., 2016)
Due to their intrinsic electromechanical coupling behavior, piezoelectric materials are widely used in sensors, actuators and other modern technologies. It is well known that piezoelectric ceramics are very brittle and susceptible to fracture. In many cases, fracture occurs at interfaces as debonding and cracks. This leads to an undesired degradation of electrical and mechanical performance. Because of the practical and fundamental importance of the problem, interface cracks in piezoelectric materials have been actively studied in the last few decades. This review provides a comprehensive survey of recent works on cracks situated at the interface of two materials, at least one of which has piezoelectric or piezoelectromagnetic properties. Different electric boundary conditions along the crack faces are discussed. The oscillating and contact zone models for in-plane straight interface cracks between two dissimilar piezoelectric materials or between piezoelectric and non-piezoelectric ones are reviewed. Different peculiarities related to the investigation of interface cracks in piezoelectric materials for the anti-plane case, for functionally graded and thermopiezoelectric materials are presented. Papers related to magnetoelectroelastic bimaterials, to steady state motion of interface cracks in piezoelectric bimaterials and to circular arc-cracks at the interface of piezoelectric materials are reviewed, and various methods used to address these problems are discussed. The review concludes with an outlook on future research directions. Завдяки властивому електромеханічному з’єднанню п’єзоелектричні матеріали широко використовуються в датчиках, приводах та інших сучасних технологіях. Загальновідомо, що п'єзоелектрична кераміка дуже крихка і чутлива до руйнування. У багатьох випадках руйнування відбувається на межах розділу у вигляді роз’єднання та тріщин. Це призводить до небажаного погіршення електричних і механічних характеристик. Через практичну та фундаментальну важливість проблеми, тріщини розділу в п’єзоелектричних матеріалах активно вивчаються в останні кілька десятиліть. Цей огляд містить вичерпний огляд останніх робіт з тріщин, розташованих на межі розділу двох матеріалів, принаймні один з яких має п’єзоелектричні або п’єзоелектромагнітні властивості. Обговорюються різні електричні граничні умови вздовж берегів тріщини. Розглянуто моделі коливальної та контактної зони для плоских прямих тріщин розділу між двома різнорідними п’єзоелектричними матеріалами або між п’єзоелектричними та неп’єзоелектричними. Представлено різні особливості, пов’язані з дослідженням міжфазних тріщин у п’єзоелектричних матеріалах для антиплоского корпусу, для функціонально градієнтованих і термоп’єзоелектричних матеріалів. Оглядаються статті, пов’язані з магнітоелектропружними біматеріалами, стаціонарним рухом тріщин розділу в п’єзоелектричних біматеріалах і круговими дуговими тріщинами на межі розділу п’єзоелектричних матеріалів, а також обговорюються різні методи, які використовуються для вирішення цих проблем. Огляд завершується поглядом на майбутні напрямки досліджень.
Міжфазні тріщини в п’єзоелектричних матеріалах
Keywords: piezoelectric materials; п’єзоелектричні матеріали; interfacial cracks; міжфазні тріщини